UI/UX DESIGN OF "PANAHIN AJA" APPLICATION TO SIMPLE THE SCORING SYSTEM AT ARCHERY SPORT IN BOGOR - Ganiy, Maheswara Titan; Razi, Aria Ar (eProceedings of Art & Design, 2024)
Archery has been practiced as a sport for a very long time. Initially, it was a tool for hunting andfighting. Archery was also used as a weapon of war for centuries, and to this day, archery is officially asporting event held all over the world. This international archery tournament is a subject of great interestin many areas, as there are many types of bows available and the archery industry has ongoing technologyto help archers achieve their goals. Archery is counted as the safest sport with the lowest risk of injury.Just shooting arrows with a bow and arrow makes the method of archery competition very simple andeasy. The most common and real problem found in the archery arena today is that of the scoring process,where errors are often found in writing inputs to archery results, resulting in re-scoring and re-scoring.resulting in inaccurate playing positions that require Data listed on the position board. So the author triesto create a UI/UX design that is expected to continue to create an online application to solve this problem.Using qualitative methods, the author tries to find an answer to the question of how to minimize humanerror in the archery competition. the color guide will help Archer choose the correct score he wants toenter. Keywords: archery, scoring, online platform, UI/UX